Deep Edu: A Deep Neural Collaborative Filtering for Educational Services Recommendation - Ullah, Farhan; Zhang, Bofeng; Khan, Rehan Ullah; Chung, Tae Sun; Attique, Muhammad; Khan, Khalil; Khediri, Salim El; Jan, Sadeeq (IEEE Access, 2020)
In the modern world, people face an explosion of information and difficulty to find the right choice of their interest. Nowadays, people show interest in online shopping to meet their demands increasingly. For researchers and students, finding and buying the desired books from online shops is very tedious work. Recently Recommender System is an excellent tool to deal with such problems, but the Recommender System is suffering from multiple problems such as data sparsity, cold-start, and inaccuracy. To address these problems, we propose Deep Edu a novel Deep Neural Collaborative Filtering for educational services recommendation. A Deep Edu architecture consists of three parts of a Deep Neural Network model (such as input layer, a multilayered perceptron, and an output layer). The Deep Edu provides the following contributions: first, the users' identifier and books identifier features are mapped into N-dimensional dense embedding vectors, second, the Multi-Layer-Perceptron (MLP) takes the N-dimensional and non-linear features. To increase the performance of Deep Edu in all metrics, we proposed the advance Loss function. Equipped with the following, Deep Edu not only capable of learning the N-dimensional and non-linear interactions between users' identifier and books identifier, but moreover, it also considerably mitigates the cold-start, data sparsity, and inaccuracy problem. Over significant experiments performed on real-world good books dataset, the results show that Deep Edu's recommendation performance obviously outperforms existing Educational services recommendation methods.
Keywords: Educational services; Multi layer perceptron; Multi-layered Perceptron; Neural network model; Nonlinear features; Nonlinear interactions; Online shopping; Recommendation performance; Deep learning; deep neural collaborative filtering; educational; services; services recommendation